Alumni perspectives on a boarding school outdoor education programme. Issue 2 (2nd April 2020) - Beames, Simon; Mackie, Chris; Scrutton, Roger
ABSTRACT: Experiences of outdoor education are believed to have significant impacts on participants, but research on the lasting influences of extended programmes is limited. Gordonstoun School, an independent residential school founded by Kurt Hahn in 1934, provides a rich legacy of outdoor education against which to explore any enduring outcomes. Drawing on data from an online survey ( n = 1174) and focus group interviews ( n = 50) with alumni from Gordonstoun, this research characterises the defining features of their out-of-classroom learning and investigates the long-term influences of this 'broader curriculum'. Out-of-classroom learning is seen to have had an overwhelmingly positive impact on former pupils, with expeditions cited as the most influential experience. The expectation that all students engage in a range of challenging situations and the importance of authentic opportunities for responsibility are identified as two particularly critical elements which have lasting influences on students. These findings have strong articulation with existing research and can be used to inform effective programme design.